OVERVIEW OF ENVIRONMENTAL HEALTH MANAGEMENT AT TOTO KABILA REGIONAL GENERAL HOSPITAL (RSUD) - Adam, TaufikHidayatullah; Arpin; Nurkamiden, Srikit S. (LP2M Universitas Bina Mandiri Gorontalo, 2024)
Environmental health in hospitals is a very important thing to pay attention to. Therefore, environmental health management in hospitals must be carried out systematically and continuously to ensure that hospitals provide a safe, clean and healthy environment for patients, medical staff and visitors.This research was conducted in the Environmental Sanitation unit of Toto Kabila Regional General Hospital using a qualitative approach and the type of research used in this study is descriptive research. The data collection method obtained or collected directly in the field by the researcher. In this study, primary data was obtained from interviews with research subjects who are directly involved in the management of environmental health at Toto Kabila Regional General Hospital. The informants interviewed were environmental health officers in the supporting structure of Toto Kabila Hospital. As a result of the research, information was obtained that the waste management process at Toto Kabila Hospital involved many parties. Waste was separated based on the type of waste available, including domestic waste, infectious and non-infectious waste. Management of liquid waste, infectious waste and domestic (non-medical) waste at Toto Kabila Regional Hospital is separated based on type, including: 1). Liquid waste is managed by IPAL and then water quality checks are routinely carried out in the laboratory; 2). Infectious waste is separated into sharp and non-sharp waste. Non-sharp infectious waste is managed using yellow bags and sharp infectious waste is disposed of in a safety box; 3). Domestic waste (non-medical waste) is managed using black bags.